2006
DOI: 10.1583/06-1835.1
|View full text |Cite
|
Sign up to set email alerts
|

Access for Endovascular Aneurysm Repair

Abstract: Despite advancement in stent-graft technology, access-related problems continue to occur during endovascular repair of aortic aneurysms. Various techniques have been adopted to overcome difficult access situations, however. To survey these developments in arterial access, we performed a systematic literature review from 1994 through 2005 to identify relevant articles pertaining to endovascular access techniques and complications. Excessive iliac tortuosity, circumferential vessel wall calcification, significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 68 publications
0
53
0
3
Order By: Relevance
“…4 Until recently, several alternative approaches for achieving adequate TEVAR access have been described. [2][3][4][5][6] Although none of them have demonstrated superiority, retroperitoneal approach to the iliac arteries seems to be the most popular approach. 5 In this study, we compare the TEVAR procedure using the retroperitoneal approach with those using direct femoral access at our center.…”
Section: Introductionmentioning
confidence: 99%
“…4 Until recently, several alternative approaches for achieving adequate TEVAR access have been described. [2][3][4][5][6] Although none of them have demonstrated superiority, retroperitoneal approach to the iliac arteries seems to be the most popular approach. 5 In this study, we compare the TEVAR procedure using the retroperitoneal approach with those using direct femoral access at our center.…”
Section: Introductionmentioning
confidence: 99%
“…Common causes of aortic access difficulties include iliac arteries with naturally small calibers or that have narrowed because of extensive atherosclerosis or calcifications. Certain options have been developed over the years in attempts to surmount these difficulties, including intra-abdominal tunnels or conduits; 6 retroperitoneal conduits; 7 conduits constructed with the aid of video vascular surgery; 8 iliac reconstruction surgeries or bypasses, 9 and angioplasty of the iliac arteries with or without stents. 10 Iliofemoral endarterectomy, 1 dissection and direct puncture of the aortoiliac segment, 9,11 and utilization of internal conduits 2,3,12 have also been described.…”
Section: Discussionmentioning
confidence: 99%
“…The EUROSTAR registry reported access problems in 13% of patients selected for EVAR, which along with migration was the leading cause of a 2% primary conversion rate. 2 Access route problems including excessive iliac tortuosity, circumferential vessel wall calcifi cation, signifi cant occlusive disease, and small-caliber vessel have all been described, 2 with various methods to overcome these problems. Criado et al reported use of a 10-mm diameter Dacron graft as an iliac conduit, which provides suffi cient luminal space for the introduction of all delivery systems.…”
Section: Discussionmentioning
confidence: 99%